2016
DOI: 10.21273/hortsci10962-16
|View full text |Cite
|
Sign up to set email alerts
|

Crop Load Density Affects ‘York’ Apple Juice and Hard Cider Quality

Abstract: Additional index words. Malus 3domestica, phenolic, polyphenol, tannin, titratable acidity, yeast assimilable nitrogen Abstract. To assess the impact crop load has on hard cider chemistry, 'York' apple (Malus 3domestica Borkh.) trees were hand thinned to three different crop loads: low [two apples per cm 2 branch cross-sectional area (BCSA)], medium (four apples per BCSA), and high (six apples per BCSA). Higher crop loads produced smaller, less acidic fruit that were slightly more mature. In juice made from fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 17 publications
0
23
0
Order By: Relevance
“…Arg was the most abundant amino acid, on average, with the highest proportion being 4.45% of total NMR signals in the cherries juice samples, and the lowest proportion being 1.67% of total NMR signals in apple juice samples. While the proportions of amino acids observed in a juice sample from a given variety may be influenced by growing season [21,22], crop load [23], geographical origin, and other factors [16], our data provide insight as to the extent of variation for each amino acid, and the ranges of relative presence of amino acids that could be expected in different types of fruit juices.…”
Section: Amino Acid Profile: Assignment Of the Interest Peaks And Stamentioning
confidence: 80%
“…Arg was the most abundant amino acid, on average, with the highest proportion being 4.45% of total NMR signals in the cherries juice samples, and the lowest proportion being 1.67% of total NMR signals in apple juice samples. While the proportions of amino acids observed in a juice sample from a given variety may be influenced by growing season [21,22], crop load [23], geographical origin, and other factors [16], our data provide insight as to the extent of variation for each amino acid, and the ranges of relative presence of amino acids that could be expected in different types of fruit juices.…”
Section: Amino Acid Profile: Assignment Of the Interest Peaks And Stamentioning
confidence: 80%
“…The total polyphenols concentration in the raw juice (Table ) was lower than that for common Spanish cider apples (0.8 to 1.3 g/L) (Juan J. Mangas et al., ) but higher than that for ‘York’ apples from Virginia harvested in 2013 (0.215 ± 0.0121 g/L) (Thompson‐Witrick et al., ). Differences in polyphenol concentrations are not unexpected, as apple cultivar, climate, and cultural practices affect the total polyphenols concentrations in apples (Peck et al., ). The total polyphenol concentrations in the four different samples were significantly different from each other ( P < 0.0001).…”
Section: Resultsmentioning
confidence: 99%
“…These benefits have led to interest in maximizing polyphenol concentrations in products such as cider (Thompson-Witrick et al, 2014). The concentrations of polyphenols in cider differ by apple variety, cultivation practices, maturity, storage and transportation conditions of apples, and the processing and fermentation techniques (Candrawinata, Blades, Golding, Stathopoulos, & Roach, 2012;Peck, McGuire, Boudreau, & Stewart, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Asparagine was the most abundant amino acid, on average, with the highest proportion being 49.7 ± 0.6% of the total amino acids in the Newtown Pippin sample, and the lowest proportion being 4.0 ± 0.04% of the total amino acids in the Golden Delicious sample. While the proportions of amino acids observed in a juice sample from a given cultivar may be influenced by growing season , crop load , site, rootstock and other factors , our data provide insight as to the extent of variation for each amino acid, and the ranges of relative concentrations of amino acids that could be expected in apple juice. The predominance of asparagine among all other amino acids was consistent with previous studies , although some prior research also reported threonine being the predominant amino acid (53.4%) in Fuji apple juice and aspartic acid being the major amino acid (41.1%) in Brazilian dessert apples .…”
Section: Resultsmentioning
confidence: 84%